2000
DOI: 10.1046/j.1365-2842.2000.00532.x
|View full text |Cite
|
Sign up to set email alerts
|

Impression pressures against teeth in a partially edentulous model with a mobile tooth: influence of impression tray design

Abstract: The purpose of the present study was to examine the effect of custom tray designs on local pressures against teeth during the impression procedure. In a previous study, a partially edentulous simulation model with a mobile tooth was used, and the effect of custom tray designs on the displacement of the mobile tooth was examined during the impression procedure. Based on that study's results, we have assumed that the differences in impression pressures between the labial and the lingual sides of a mobile tooth c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 3 publications
1
7
0
Order By: Relevance
“…The space affects the impression pressure occurring during impression procedure, which would displace the tooth and ridge mucosa. It was reported that using trays with a thicker space for impression materials lessened the impression pressures (3, 7–9). Furthermore, Nishi et al.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The space affects the impression pressure occurring during impression procedure, which would displace the tooth and ridge mucosa. It was reported that using trays with a thicker space for impression materials lessened the impression pressures (3, 7–9). Furthermore, Nishi et al.…”
Section: Discussionmentioning
confidence: 99%
“…The simulation models and devices for measuring displacement of the mobile tooth and impression pressure against the subject teeth, which were used in previous studies (2, 3), were prepared in the present study. The two simulation models were prepared using a simulated periodontal ligament made of silicone rubber for the left central incisor (mobile incisor) in a mandibular plastic model with six anterior teeth (Model 550)*.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations